Protecting environmental defenders to prevent pandemics - Aruta, John Jamir Benzon R *; Guinto, Renzo R *; Clements, Gopalasamy Reuben *; Jemilah, Mahmood * (Elsevier, 2022)
Although the jury remains out with regard to the origin of the ongoing COVID-19 pandemic,1 this global health crisis is a stark reminder of the continuous threat of emerging infectious diseases, and the need to tackle their upstream drivers (eg, deforestation and illegal wildlife trade). However, proposals for preventing pandemics at the source2 tend to focus on high-level policies and actions, with relatively little support afforded to ground-level environmental defenders, who are arguably the most important front-line defence in stopping future zoonotic spillovers. Through sustained involvement in activities that reduce deforestation and biodiversity loss (eg, lobbying against powerful industries or politicians, and patrols to curb illegal harvesting), environmental defenders face increasing duress, ranging from occupational burnout to life-threatening attacks.3 Protecting the welfare of environmental defenders must be part of the solution to preventing future pandemics.